Flexible and specific contributions of thalamic subdivisions to human cognition. (May 2021) - Antonucci, Linda A.; Penzel, Nora; Pigoni, Alessandro; Dominke, Clara; Kambeitz, Joseph; Pergola, Giulio
Highlights: A cognitively flexible set of brain regions is involved with the thalamus in several cognitive domains. Some thalamic subdivisions show cognitive specificity and remarkable laterality patterns. To capture the complexity of thalamus involvement in cognition, it should be considered an "ensemble" of brain crossroads. Abstract: The thalamus participates in multiple functional brain networks supporting different cognitive abilities. How thalamo-cortical connections map onto the architecture of human cognition remains an outstanding question. The aim of this meta-analysis is to map co-activation between thalamic and extra-thalamic brain regions onto separate cognitive domains and to assess thalamic subdivision specificity within each of the cognitive domains considered. We parsed 93 fMRI studies into twelve cognitive domains. Signed Differential Mapping served to obtain co-activation maps. We then projected the contribution of thalamic subdivisions onto a thalamic atlas to assess cognitive domain specificity. A set of brain regions was flexibly involved with thalamus in several cognitive domains. Thalamic subdivisions showed ample cognitive heterogeneity. Our proposed model represents thalamic involvement in cognition as an "ensemble" of functional subdivisions with common cell properties embedded in separate cortical circuits rather than a homogeneous functional unit.